CHARACTERISTICS OF BREAKING WAVES AND ANALYSIS OF SEDIMENT TRANSPORT IN TELUK KENDARI - Koko Ondara; Semeidi Husrin (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
One of the problems that often occured in the bay area is a sedimentation process that occurred continuously, causing silting. The movement of sediment material in the process of sedimentation is influenced by the movement of the water flow like the tides, winds, currents and waves. The aim of this study was to determine the characteristics of the hydrodynamic conditions, particularly the distribution pattern and the capacity of the sediments in the Kendari Bay with oceanographic modeling approach. Bathymetry data measured at the site of the research conducted in August 2015. The analysis of distribution patterns of sedimentation, sedimentation capacity, wave hindcasting, wind data and tidal data using software, hindcasting results indicate the dominant wind direction coming from the east. Type tides in Kendari Bay is a mixed mainly semiurdunal tides. The concentration of suspended sediment at low tide is greater than at high tide. Keywords: sediment transport, wave characteristics, Kendari Bay, hydro - dynamics, mike21